A self-reported questionnaire for quantifying illness symptoms in elite athletes - Matthews, A.; Pyne, D.; Saunders, P.; Fallon, K.; Fricker, P. (Open Access Journal of Sports Medicine, 2010)
To develop and evaluate a questionnaire that quantifies the self-reported frequency, duration and severity of illness symptoms in highly-trained athletes. We examined whether runners had more symptoms than recreationally-active individuals, and whether runners more prone to illness were undertaking more strenuous training programs.